2006
DOI: 10.1002/hed.20312
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoepithelioma-like carcinoma of minor salivary gland: A case report with immunohistochemical and in situ hybridization studies

Abstract: Our case suggests potential pathogenic implications of both c-KIT and EBV in LEC of the minor salivary gland that can be cured by the combination of surgery and radiotherapy and has a very favorable long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Among these, LMP-1 has a driving role. Expression of LMP-1 prevents apoptosis, induces abnormal cell proliferation, deregulates epithelial growths and inhibits differentiation, with the epithelial cells showing the features of transformed cells [34]. However, the expression of this protein was observed only in few EBV-linked salivary LELC from Asian patients and our case is the first one in which LMP-1 positivity was detected in a Western patient.…”
Section: Discussionmentioning
confidence: 75%
“…Among these, LMP-1 has a driving role. Expression of LMP-1 prevents apoptosis, induces abnormal cell proliferation, deregulates epithelial growths and inhibits differentiation, with the epithelial cells showing the features of transformed cells [34]. However, the expression of this protein was observed only in few EBV-linked salivary LELC from Asian patients and our case is the first one in which LMP-1 positivity was detected in a Western patient.…”
Section: Discussionmentioning
confidence: 75%
“…The implication with EBV, since EBV was isolated in >90% of endemic PLEC patients, has proposed a possible function for the virus in the etiopathogenesis of PLEC but the association remains in dispute, taking consideration that EBV usually was undetected in the non-endemic PLEC cases 27 . Additional research papers investigating PLEC neoplasms, reported viral presence in clonal episomal form and viral LMP-1 oncoprotein expression, supporting EBV role in PLEC tumorigenesis 35,36 . Moreover in support of PLEC and EBV association, it has been suggested that EBV is possible to play a role in younger patients in Asian populations, because it was previously reported that primary infection of EBV in children of families with lower socioeconomic status was an early event 37 .…”
Section: Discussionmentioning
confidence: 86%
“…In the previous studies, p53 status was studied in only two cases. One case with EBV showed p53 expression in only 25% of the tumor cells, suggesting wild type [5]. In contrast, one EBVnegative LEC showed overexpression of p53 on immunohistochemistry [14].…”
Section: Discussionmentioning
confidence: 93%